Revisitando o passado : narrativas afrocentradas de Eliana Alves Cruz para (re)pensar literatura e história - Cereza, Felipe Aquiles Cereza (2023)
Literature produced by black authors has critically reviewed Brazilian colonial history, seeking to rewrite the past through the lens of a present time filled with inequality, discrimination and racial genocide features, drawing back to the times of slavery. In this sense, one can find in the novels O crime do Cais do Valongo and Nada digo de ti, que em ti não veja, by Eliana Alves Cruz (2018b; 2020a), literary representations of black individuals subjected to racial and colonial attitudes, typical of the XVIII and XIX centuries. Thus, this study aims at investigating what Afro-centered perspectives may reveal in the aforementioned novels, attempting to understand how such perspectives contribute to the renewal of both literary and historic occidental discourses. To do so, this study analyzes the narrator’s and character’s points of view, highlighting their narrative role grounded in the literary studies of Cândido (2007), Genette (1995) and Reis (2013), among others. Evoking a dialogue between the analyses of both novels, this study seeks to interpret racial, ethnic and cultural relationships within the theoretical approach of the cultural studies by Gonzalez (1998), Hall (2008), Nascimento (1978) and Mbembe (2016). Regarding the historic and literary discursive nature, the pertinence and critical contributions to the field of Cultural History are analyzed, according to Pesavento (2004), and to Literature, by the perspective of the Latin American historical novel (NNH), according to Aínsa (1994) and Menton (1993), and also addressed in Santos’ studies (2017), as well as of the literature of black authorship, oriented by aspects and reflections raised by Cuti (2010), Duarte (2010) and Evaristo (2009). This study argues that the two narratives of Eliana Alvez Cruz analyzed reflect an Afro-centered view of the world, due to the fact that they represent ethnic-cultural and Afro-identified individuals, highlighting the violent features that conform and renew the history of slavery, as well as reveal the fight, resistance and survival stories of such marginalized individuals. Conversely, the analyses suggest that the reading method of NNH is applicable, yet demanding more dialogues with other areas of study to better explore the meaning potentialities of the novels. In contrast, critical studies on literature produced by black authors serve as productive reading guides to explore the meanings Eliana Alves Cruz tried to convey in her work, which reveals an ethnic-cultural, African and Afro-centered universe